Rancangan Aplikasi E-Learning Pada Sekolah Menengah Pertama - Yoyok Rohani - AMIK BSI Yogyakarta (LPPM Universitas Bina Sarana Informatika, 2015)
Abstract - We have implemented a system of teaching and learning in schools is confined to the classroom and school environment. Students get the subject matter and the task of the teacher in the classroom and look for references in the school library so that the learning process of learning not use the Internet. Internet currently allows to be used to help in the learning process. E-learning is one of the applications to help web-based teaching and learning that is accessible to the internet. Expectations for e-learningadalah improve the quality of communication between students and teachers as in e-learningmemungkinkan two-way communication and help teachers in the distribution of materials and the provision of learning tasks so that the system can take place effectively and efficiently, and students can learn independently. With the method of observation, interviews and literature then e-learningdikembangkan using PHP AND MySQL database program, the display design was designed using Adobe Dreamweaver CS6. Tests were conducted using a Black Box Testing. While the result is the availability of applications supporting teaching and learning activities that can be accessed online.Keywords: E-Learning, PHP, Dreamweaver CS, Internet, MySql Abstrak - Saat ini sistem belajar mengajar yang diterapkan di sekolah hanya terbatas pada kelas dan lingkungan sekolah. Siswa mendapatkan materi pelajaran dan tugas dari guru di dalam kelas dan mencari referensi di perpustakaan sekolah sehingga proses belajar belajar belum memanfaatkan internet. Internet saat ini memungkinkan untuk dimanfaatkan membantu dalam proses belajar mengajar. E-learning adalah salah satu aplikasi untuk membantu belajar mengajar berbasis web yang dapat diakses dengan internet. Harapan adanya sistem e-learningadalah meningkatkan kualitas komunikasi antara siswa dan guru karena di dalam e-learningmemungkinkan komunikasi dua arah dan membantu guru dalam pendistribusian materi serta pemberian tugas sehingga sistem pembelajaran dapat berlangsung secara efektif dan efisien dan siswa dapat belajar secara mandiri. Dengan metode observasi, wawancara dan studi pustaka maka e-learningdikembangkan dengan menggunakan program PHPdan database MySQL, desain tampilan dirancang menggunakan Adobe Dreamweaver CS6. Pengujian yang dilakukan menggunakan Black Box Testing. Hasil yang dicapai adalah ketersediaan aplikasi pendukung kegiatan belajar mengajar yang dapat diakses secara online. Kata kunci: E-Learning, PHP, Dreamweaver CS, Internet, MySql